A CORRELATION STUDY BETWEEN WATCHING MOVIES HABITS AND VOCABULARY MASTERY - Terang Cahaya Benderang; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
This research aimskat finding out whetherktherekiska significant correlation between the habit oflwatchinglEnglish moviesland vocabularylmastery at seventh-grade students of SMPlNegeril1 Colomadu. Thislresearchlwas conducted atlthe seventh gradelof SMPlNegeril1 Colomadulin 2020/2021 AcademiclYear. The researcher used a correlational study which was conducted from December 2020 until May 2021 at the class of VII E. The study was divided into two phases, each of which included two meetings. Each meeting also included data collection through the use of a Google Form. In order tolanalyze quantitativeldata, the researcherlusedlquestionnaires and tests. Based onlthelresult oflthe study, it showedlthatlthe coefficient of the correlationlbetween watchinglmovie habits andlvocabularylmastery was 0.685 withlthe levellsignificant 5% for theldegree oflfreedom (df) = 29 the rltable is 0.367, and the level significant 1% for theldegreeloflfreedom (df) = 29 the rltable is 0.470. By using coefficient correlation, criteria 0.685 is classified to interval 0.600 – 0.800 in the indexes of correlation which is sufficient correlation. It means that r-observation (rxy) was higher than r table and it was concluded that there was alsignificant correlationlbetween watchinglmovie habits andlvocabulary mastery at the seventh-gradelstudents of SMP Nl1 Colomadu inlthe 2020/2021 academiclyear.   Keywords: Vocabulary Mastery, Watching Movie Habits, Correlational Study